Differentiable MadNIS-Lite - Heimel, Theo; Mattelaer, Olivier; Plehn, Tilman; Winterhalder, Ramon (SciPost physics, 2025)
SciPost Journals Publication Detail SciPost Phys. 18, 017 (2025) Differentiable MadNIS-Lite
Veröffentlicht: 15. Januar 2025
Gesehen am 16.07.2025